(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: To assess of the current status of knowledge and practice in caring for children under 5 years of age with acute diarrhea of mothers and some related factors at the International medical Center of National Children’s Hospital in 2022 Methods: A cross-sectional descriptive study on 315 eligible subjects. Results: The general knowledge reached a good level (74.2%), in which 95.9% of mothers had the correct concept of diarrhea. The general practice a good (55.9%), in which 62.2% of mothers had good practice of using Oresol at home. Some factors related to poor knowledge and practice are the education level from upper secondary school or below (OR 2.45; 95%CI 1.455-5,236; p<0,05), occupation group Farmer, Worker, Housewife (OR 2.45; 95%CI 1.455-5,236; p<0,05). OR 1.77 95% CI 1.223-3.576), the mother had only 1 child (OR 1.67; 95% CI 1.325-4.429; p<0,05). Conclusions: The rate of knowledge and general practice reaching good level is still low at 74.2% and 55.9%, respectively. Some related factors affecting knowledge and poor practice are the education level from high school or below, the occupation group Farmers, Workers, Housewives, mothers with only 1 child